2012
DOI: 10.1007/s10551-012-1503-3
|View full text |Cite
|
Sign up to set email alerts
|

Do Non-socially Responsible Companies Achieve Legitimacy Through Socially Responsible Actions? The Mediating Effect of Innovation

Abstract: This study investigates the effects on organization's financial performances of, firstly, the extent to which the organizations are involved in controversial business activities, and secondly, their level of social performance. These companies can be considered non-socially responsible given the harmful nature of the activities they are involved in. Managers of these companies may still have incentives to pursue socially responsible actions if they believe that engaging on those actions will help them to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 70 publications
3
52
1
1
Order By: Relevance
“…When the mediator (Figure 3) is added, the influence of CSR hardly decreases, but a significant direct effect on objective performance is maintained (c' = 0.213; t = 2.17), in accordance with previous research. Moreover, it is shown that innovation (H1op: a*b) does not mediate the relationship between CSR and objective performance in contrast to previous findings (Blanco et al, 2013;Hull & Rothenberg, 2008;Surroca et al, 2010).…”
Section: Structural Modelcontrasting
confidence: 96%
See 1 more Smart Citation
“…When the mediator (Figure 3) is added, the influence of CSR hardly decreases, but a significant direct effect on objective performance is maintained (c' = 0.213; t = 2.17), in accordance with previous research. Moreover, it is shown that innovation (H1op: a*b) does not mediate the relationship between CSR and objective performance in contrast to previous findings (Blanco et al, 2013;Hull & Rothenberg, 2008;Surroca et al, 2010).…”
Section: Structural Modelcontrasting
confidence: 96%
“…Based on the above studies, we propose that innovation plays a mediating role between CSR and firm performance (Blanco, Guillamón-Saorín, & Guiral, 2013;Perrini, Russo, Tencati, & Vurro, 2011;Surroca et al, 2010). That is, innovation is the way in which social responsible firms can improve their performance.…”
Section: Csr and Firm Performance: The Mediating Effects Of Innovationmentioning
confidence: 99%
“…A firm's stakeholders are generally interested in PCER, yet they may be constrained by the firm's financial situation. When firms are in financial distress, they are not able to assume more responsibility [51]. Highly profitable firms are more readily able to take a pragmatic approach to legitimacy such as better-quality products to consumers and fewer emission of wastes and poisonous gases to the community [35,52].…”
Section: The Influence Of Past Performance On the Relationship Betweementioning
confidence: 99%
“…The concept of transparency takes part in many mediating relationships, especially in the field of human resources (Sharma, 2009;Vogelgesang, Leroy, & Avolio, 2013) or trust in government (Song & Lee, 2015). Several authors, such as Surroca, Tribo, & Waddock, (2010), Huang and Lien (2012) or Blanco, Guillamón-Saorín, and Guiral, (2013), have previously raised the inclusion of mediating effect explanations in the relationship between social and financial performance. However, previous studies have focused on the role of innovation.…”
Section: O D E L a N D H Y P O T H E S E S Developmentmentioning
confidence: 99%